Enzymatic Degradation of Bombyx mori Silk Materials: A Review - Guo, Chengchen; Li, Chunmei; Kaplan, David L (Biomacromolecules, 2020)
As a biomaterial, silk presents unique features with a combination of excellent mechanical properties, biocompatibility, and biodegradability. The biodegradability aspects of silk biomaterials, especially with options to control the rate from short (days) to long (years) time frames in vivo, make this protein-based biopolymer a good candidate for developing biodegradable devices used for tissue repairs and tissue engineering, as well as medical device implants. Silk materials, including native silk fibers and a broad spectrum of regenerated silk materials, have been investigated in vitro and in vivo to demonstrate degradation by proteolytic enzymes. In this Review, we summarize the findings on these studies on the enzymatic degradation of Bombyx mori (B. mori) silk materials. We also present a discussion on the factors that dictate the degradation properties of silk materials. Finally, in future perspectives, we highlight some key challenges and potential directions toward the future study of the degradation of silk materials.